(untitled) (Research, Society and Development, 2022)
The climatic and environmental imbalance, the result of the intensification and expansion of the capitalist planetary economic system, is increasingly worrying. Alarming data revealed by scientists worldwide, mobilize countries in favor of reducing these effects, for the maintenance of the human species. The objective of this article is based on this premise, which, through exploratory research, will explain the historical context that consolidates this conjuncture, the reflexes of this trajectory in contemporary times, as well as the “resistance social networks”, which underlie the confrontation to such systemic imbalances. Focusing on the Brazilian reality, and, in particular, the insertion of capitalism in relationships in the country’s rural environment, the article will bring to the discussion the impact of rural capitalism on the struggle of peasants/rural workers; the consolidation of this capitalist insertion in the countryside through contemporary data regarding Brazilian deforestation and the consolidation of agribusiness and the production of export monocultures, which directly impact work and food security in Brazil. In order to present some alternatives of resistance existing in Brazil, in this worrying scenario, as a way of thinking and systematizing strategies for overcoming it.